The Impact of Online Learning Media on Students' Learning Interests in Islamic Religious Education Subjects during the Covid-19 Period - Kartika Kartika; Sahraini Sahraini; Taqwa Taqwa (Journal of Indonesian Islamic Studies, 2022)
The type of research used in this study was quantitative, with a population of 178 students and a sample of 34 students. Data collection techniques used are; observation, questionnaires, and documentation, as well as data analysis techniques used by researchers with the help of SPPS version 24. The results of the study found that: an analysis of the use of courageous learning media in class VII Islamic Religious Education subjects at SMP Negeri 6 Palopo, which is located in the sufficient category with percentage value of 68%, analysis of students' learning interest during the covid-19 period of Islamic Religious Education (PAI) class VII at SMP Negeri 6 Palopo which is located in the sufficient category with a percentage value of 56%, as well as an analysis of the effect of learning media on the interest of learning participants students during the covid-19 period of Islamic Religious Education (PAI) class VII at SMP Negeri 6 Palopo, the results of data analysis with the help of SPSS version 24, obtained a value of Y = 27.820 β + 0.748 X. Then test the coefficient of determination to find out how much the level variables X and Y the value obtained is R2 = 0.286 = 28.6%, meaning that the independent variable of online learning media influences hi the dependent variable of students' interest in learning is 28.6% and the rest is influenced by other variables not included in this study.